The Development of Philosophical Thought in the Greek Colonies on the Territory of Ukraine (the Case of Olbia) - Dodonov, Roman (Skhid : analitychno-informat͡s︡iĭnyĭ z͡h︡urnal, 2025)
The article is devoted to analysing the role of ancient Greek thinkers in the history of Ukrainian philosophy. Ukrainian philosophical thought, like all Ukrainian culture, is based on two fundamental sources: ancient cosmism and the Christian belief in the immortality of the soul. This makes Ukrainian philosophy part of the pan-European tradition. The search for European roots leads to the need to study the philosophical views of the population of ancient Greek colonies in the territory of modern Ukraine. Taking into account the temporarily occupied territories of Ukraine, the emphasis is placed on the largest of the Greek colonies available today – Olbia, the ruins of which are located near the village of Parutino in the Mykolaiv region. The article is written within the framework of the interdisciplinary methodology of the Ukrainian studies paradigm and takes into account the results of research in classical ancient literature (Herodotus, Diogenes Laertius, Dion Chrysostom, Ovid), prosopographic, epigraphic and archaeological discoveries. The first colonists in Olbia were citizens of Miletus, a city in Ionia with a world-famous philosophical school. It is hypothesised that the Olbiopolitans were familiar with the natural philosophical views of the metropolis: Thales, Anaximander, Anaximenes. This is indirectly indicated by the prevalence of graffiti with the name Anaximander in Olbia. Researchers have discovered bone plates with inscriptions such as “Life-Death-Life-Truth”, “Peace-War”, “Truth-Deception”, “Body-Soul”, “Dionysus-Orphics” testify to the popularity among the Olbiopolitans of ideas of Orphism and Pythagoreanism about the immortality of the human soul, the possibility of resurrection of the dead and “eternal return”. In the Hellenistic period, Dion Chrysostom wrote in his “Oratio Borysthenitica” about the philosophical conservatism of the Olbiopolitans, who loved Homer, although they were also familiar with the views of Plato. It is emphasised that Greek philosophy spread among the barbarian population of the Northern Black Sea region through Olbia and other colonies. The conclusion is made about the connection between ancient cosmism through Neoplatonism and early Christian ideas about the world, God, and man, which became decisive for the later Ukrainian philosophical tradition.